Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1073/pnas.0506179102
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-observed photosynthetic trends across boreal North America associated with climate and fire disturbance

Abstract: We analyzed trends in a time series of photosynthetic activity across boreal North America over 22 years (1981 through 2003). Nearly 15% of the region displayed significant trends, of which just over half involved temperature-related increases in growing season length and photosynthetic intensity, mostly in tundra. In contrast, forest areas unaffected by fire during the study period declined in photosynthetic activity and showed no systematic change in growing season length. Stochastic changes across the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
494
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 593 publications
(535 citation statements)
references
References 34 publications
35
494
4
2
Order By: Relevance
“…However, the timing, magnitude and relative importance of these climate controls varies substantially between and within biomes, consistent with differences in climate responses between plant functional types observed in earlier studies [15,31]. Simple correlations suggest that summer temperature is the dominant control of summer anomalies of photosynthetic activity in the cool boreal and Arctic regions, whereas spring and summer soil moisture availability is the main control of summer photosynthetic activity across the continental interiors in the northern temperate grasslands and to a lesser extent in croplands ( Figure 5).…”
Section: Spatially Heterogeneous Controls Of Interannual Variability supporting
confidence: 65%
See 4 more Smart Citations
“…However, the timing, magnitude and relative importance of these climate controls varies substantially between and within biomes, consistent with differences in climate responses between plant functional types observed in earlier studies [15,31]. Simple correlations suggest that summer temperature is the dominant control of summer anomalies of photosynthetic activity in the cool boreal and Arctic regions, whereas spring and summer soil moisture availability is the main control of summer photosynthetic activity across the continental interiors in the northern temperate grasslands and to a lesser extent in croplands ( Figure 5).…”
Section: Spatially Heterogeneous Controls Of Interannual Variability supporting
confidence: 65%
“…Earlier studies have reported an apparent shift towards increased moisture limitation of vegetation productivity with continued warming since the the early 1990s across much of the temperate and boreal ecosystems [4,15,21]. Our results indicate that the interannual association between climate (temperature, moisture and snow) and NDVI variability has not changed over time ( Figure 7) and thus there is no evidence for consistent regional-scale temporal shifts from temperature to moisture limitation with recent warming on a year-to-year basis and at the grid box level.…”
Section: Spatially Heterogeneous Controls Of Interannual Variability mentioning
confidence: 99%
See 3 more Smart Citations